Principal’s Leadership Strategies in Enhancing Students’ Religious Competence: A Case Study at Madrasah Aliyah - Ningsih, Ika Rahayu; Darim, Abu; Srinio, Fuad; Jannah, Simiftahul (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2025)
This research addresses the problem of how school principals manage and improve students’ religious competence, which is often overlooked in the development of educational quality. The purpose of this study is to find out: (1) how the headmaster plans to increase students’ religious competence, (2) how the headmaster organizes the efforts, (3) how the headmaster carries out the plan, and (4) how the headmaster evaluates the process. Using a qualitative methodology, the study collects data through field observations, interviews, recordings, written notes, and documentation to ensure reliability and depth of information. The findings reveal that principals implement strategies and policies involving planning, organization, implementation, and evaluation which result in graduates capable of actively engaging in society through religious activities; student admission is conducted both online and offline with assessments also integrated digitally, while religious culture is strengthened through active participation in Islamic events such as Isra’ Mi’raj, Muharram, Ramadhan activities, Mawlid, Qur’anic recitation, and Khotmil Qur’an programs. These results indicate that the principal’s leadership not only enhances students’ religious competence but also contributes to building a strong religious culture in schools, offering practical models for other educational institutions to adopt to integrate religious competence with broader academic achievement.